Molecular Analysis of the 18S rRNA Gene of Cryptosporidium Parasites from Patients with or without Human Immunodeficiency Virus Infections Living in Kenya, Malawi, Brazil, the United Kingdom, and Vietnam - Gatei, Wangeci (American Society for Microbiology, 2003)
An 840-bp fragment of the 18S rRNA gene was used to identify Cryptosporidium spp. recovered from human immunodeficiency virus (HIV)-infected and -uninfected patients from Kenya, Malawi, Brazil, the United Kingdom, and Vietnam. Initial identification was by Ziehl-Neelsen acid-fast staining. Confirmation was by nested PCR, targeting the most polymorphic region of the 18S rRNA gene. Genotyping was by restriction endonuclease digestion of the PCR product followed by nucleotide sequencing. Among 63 isolates analyzed, four genotypes of Cryptosporidium were identified; 75% of the isolates were of the C. parvum human genotype, while the potentially zoonotic species were of the C. parvum bovine genotype (21.7%), the C. meleagridis genotype (1.6% [one isolate]), and the C. muris genotype (1.6% [one case]). HIV-infected individuals were more likely to have zoonotic genotypes than the HIV-uninfected individuals. Among the C. parvum group, strains clustered distinctly into either human or bovine genotypes regardless of the geographical origin, age, or HIV status of the patients. The intragenotypic variation observed in the C. parvum human genotype was extensive compared to that within the C. parvum bovine genotype group. The variation within genotypes was conserved in all geographical regions regardless of the patients' HIV status. The extensive diversity within genotypes at the 18S rRNA gene locus may limit its application to phylogenetic analyses.